A Bundled Payment Model for Pediatric Distal Radius Fractures: Defining an Episode of Care. Issue 3 (March 2019) - Godfrey, Jenna M.; Little, Kevin J.; Cornwall, Roger; Sitzman, Thomas J.
Abstract : Background: Distal radius fractures are the most common fracture of childhood, occurring in ∼1 per 100 children annually. Given the high incidence of these fractures, we explored feasibility of a bundled payment model. We determined the total treatment costs for each child and identified components of fracture management that contributed to variations in cost. Methods: We retrospectively reviewed all hospital and physician costs related to the treatment of closed distal radius fractures at a large academic children's hospital. We included all children age 2 to 15 years treated by an orthopaedic surgeon for an isolated closed distal radius fracture between 2013 and 2015. We compared total treatment costs by fracture management approach. We then estimated the contribution of each component of fracture management to total treatment costs using linear regression. Results: We identified 5640 children meeting the inclusion criteria, of which 4602 (81.6%) received closed treatment without manipulation, 922 (16.3%) underwent closed reduction in the clinic, emergency department, or radiology procedure suite, and 116 (2.1%) underwent treatment in the operating room. The median cost for closed treatment without manipulation was 1390 [interquartile range (IQR) 1029 to 1801], compared with 4263 (IQR, 3740 to 4832) for closed reduction and 9389 (IQR, 8272 to 11, 119) for closed reduction and percutaneous pinning ( P <0.001). In multivariable regression analysis, fracture management approach and use of the operating room environment were the largest cost drivers ( P <0.001, R 2 =0.88). Closed reduction in the clinic or emergency department added 894 (95% confidence interval, 819-969) to treatment costs, while closed reduction in the operating room added 5568 (95% confidence interval, 5224-6297). Location of the initial clinical evaluation, number of radiographic imaging series obtained, and number of orthopaedic clinic visits also contributed to total costs. Conclusions: Closed pediatric distal radius fractures treated without manipulation show small variations in treatment costs, making them well suited for bundled payment. Bundled payments for these fractures could reduce costs by encouraging adoption of existing evidence-based practices. Level of Evidence: Level III—therapeutic. Abstract : Supplemental Digital Content is available in the text.